Prevalence Indicators of Caries and Parodont Soft Tissue Diseases in Children with Congenital Heart Defects - Hamroeva Dilafruz Shukurovna (Genius Journals, 2023)
In order to study the prevalence of major dental diseases in children with congenital heart disease compared to healthy children without somatic disease, children were divided into observation and control groups. The blue and white form of congenital heart defect formed the observation group, and a dental examination was performed
Keywords: Congenital heart defect; intensity PMA index; caries; gingivitis